The Nucleus/Mitochondria-Shuttling LncRNAs Function as New Epigenetic Regulators of Mitophagy in Cancer - Li, Yan; Li, Wei; Hoffman, Andrew R.; Cui, Jiuwei; Hu, Ji-Fan (Frontiers in Cell and Developmental Biology, 2021)
Mitophagy is a conserved intracellular catabolic process responsible for the selective removal of damaged or dysfunctional mitochondria by targeting them to the autophagosome in order to maintain mitochondria quality. The role of mitophagy in tumorigenesis has been conflicting, with the process both supporting cell survival and promoting cell death, depending on the cellular context. In established tumors, cancer cells may use mitophagy to augment their metabolic requirements and enhance resistance to cell death, thereby leading to increased growth and invasiveness. This review highlights major regulatory pathways of mitophagy involved in cancer. In particular, we summarize recent progress regarding how nuclear-encoded long non-coding RNAs (lncRNAs) function as epigenetic players affecting the malignant behavior of tumors by regulating mitophagy. Finally, we discuss the potential application of regulating mitophagy as a new target for cancer therapy.